First Identification of Reinfection by a Genetically Different Variant of SARS-CoV-2 in a Homeless Person from the Metropolitan Area of Santiago, Chile. (27th April 2022) - Acuña-Castillo, Claudio; Vidal, Mabel; Inostroza-Molina, Ailen; Vallejos-Vidal, Eva; Luraschi, Roberto; Figueroa, Maximiliano; Barrera-Avalos, Carlos; Vera, Rodrigo; Vargas, Sergio; Valdes, Daniel; Maisey, Kevin; Imarai, Mónica; et al.
Abstract : The identification and tracking of SARS-CoV-2 infected patients in the general population are essential components of the global strategy to limit the COVID-19 viral spread, specifically for maintaining traceability and suppressing the resurgence of local outbreaks. Public health programs that include continuous RT-qPCR testing for COVID-19 in the general population, viral sequencing, and genomic surveillance for highly contagious forms of the virus have allowed for the identification of SARS-CoV-2 infections and reinfections. This work identified SARS-CoV-2 reinfection in a homeless person, which occurred 58 days after the first COVID-19 diagnosis. Genomic sequencing identified a different Nextstrain classification clade (20A and 20B) and PANGO lineage, with a divergence of 4 single nucleotide variants (SNVs) in S and ORF1ab genes, suggesting reinfection by different viral variants. This study is the first from the great metropolitan area of Santiago, Chile, one of the top ten countries in the world to live during the COVID-19 pandemic. We support the importance of performing intensive genomic surveillance programs in the whole population and high-risk groups, such as homeless people, nearly 20 thousand people in Chile, and have limited access to health care services and poor viral traceability.